Turkish version of the Pet Bereavement Questionnaire: Validity, reliability and psychometric properties. Issue 2 (7th February 2023) - Yüksel, Özge; Apak, Bengisu; Demirci, Öykü
Abstract: This study examined the psychometric properties of the Turkish form of the Pet Bereavement Questionnaire (PBQ). Bereaved people ( N  = 688) completed the PBQ, Grief and Meaning Reconstruction Inventory, and Traumatic Grief Inventory. Although the factor structure is consistent with the original, the Exploratory and Confirmatory Factor Analysis indicated that two items should be included in a different factor. The analyses revealed good internal consistency, split-half reliability, and concurrent validity. Subscales produced meaningful correlations with loss-related variables. The psychometric properties of the Turkish version of the PBQ indicate the measure is highly suited to measuring the symptoms of pet loss.